Liquid NanoBiosensors Enable One‐Pot Electrochemical Detection of Bacteria in Complex Matrices - Sara M. Imani; Enas Osman; Fatemeh Bakhshandeh; Shuwen Qian; Sadman Sakib; Michael MacDonald; Mark Gaskin; Igor Zhitomirsky; Deborah Yamamura; Yingfu Li; Tohid F. Didar; Leyla Soleymani (Advanced Science, 2023)
Abstract There is a need for point‐of‐care bacterial sensing and identification technologies that are rapid and simple to operate. Technologies that do not rely on growth cultures, nucleic acid amplification, step‐wise reagent addition, and complex sample processing are the key for meeting this need. Herein, multiple materials technologies are integrated for overcoming the obstacles in creating rapid and one‐pot bacterial sensing platforms. Liquid‐infused nanoelectrodes are developed for reducing nonspecific binding on the transducer surface; bacterium‐specific RNA‐cleaving DNAzymes are used for bacterial identification; and redox DNA barcodes embedded into DNAzymes are used for binding‐induced electrochemical signal transduction. The resultant single‐step and one‐pot assay demonstrates a limit‐of‐detection of 102 CFU mL−1, with high specificity in identifying Escherichia coli amongst other Gram positive and negative bacteria including Klebsiella pneumoniae, Staphylococcus aureus, and Bacillus subtilis. Additionally, this assay is evaluated for analyzing 31 clinically obtained urine samples, demonstrating a clinical sensitivity of 100% and specify of 100%. When challenging this assay with nine clinical blood cultures, E. coli‐positive and E. coli‐negative samples can be distinguished with a probability of p < 0.001.